Consensus guidelines for lumbar puncture in patients with neurological diseases - Engelborghs, Sebastiaan; Niemantsverdriet, Ellis; Struyfs, Hanne; Blennow, Kaj; Brouns, Raf; Comabella, Manuel; Dujmovic, Irena; van der Flier, Wiesje; Frölich, Lutz; Galimberti, Daniela; Gnanapavan, Sharmilee; Hemmer, Bernhard; et al. (Alzheimer's & dementia (Amsterdam, Netherlands), 2017)
INTRODUCTION: Cerebrospinal fluid collection by lumbar puncture (LP) is performed in the diagnostic workup of several neurological brain diseases. Reluctance to perform the procedure is among others due to a lack of standards and guidelines to minimize the risk of complications, such as post-LP headache or back pain. METHODS: We provide consensus guidelines for the LP procedure to minimize the risk of complications. The recommendations are based on (1) data from a large multicenter LP feasibility study (evidence level II-2), (2) systematic literature review on LP needle characteristics and post-LP complications (evidence level II-2), (3) discussion of best practice within the Joint Programme Neurodegenerative Disease Research Biomarkers for Alzheimer's disease and Parkinson's Disease and Biomarkers for Multiple Sclerosis consortia (evidence level III). RESULTS: Our consensus guidelines address contraindications, as well as patient-related and procedure-related risk factors that can influence the development of post-LP complications. DISCUSSION: When an LP is performed correctly, the procedure is well tolerated and accepted with a low complication rate.
Keywords: Cerebrospinal fluid; Back pain; Lumbar puncture; Consensus guidelines; Evidence-based guidelines; Post-LP complications; Headache